Exploring The Perceived Role of Entrepreneurship Education among Learners in South Africa (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study examines how South African Further Education and Training (FET) Business Studies learners view the role of entrepreneurship education in their decision-making process when choosing a career. However, its precise influence on the career decisions of FET Business Studies learners as a vital portion of the future labour force remains unstudied mainly, especially in South Africa.Design/ Methodology/ Approach: This study used a qualitative case study research design to explore the views of FET Business Studies learners on entrepreneurship education and how it affects their choice of employment. Rich, in-depth insights were obtained through focus group discussions with a purposefully selected sample of 30 FET learners enrolled in Business Studies from three distinct South African secondary schools. The focus group discussions comprised six learners per group from each grade (Grades 10, 11, and 12).Research Limitation: While focus groups allow for rich discussion, the breadth of topics covered in each session may have been limited by time constraints. As a result, some aspects of the learners' experiences and perspectives may not have been fully explored.Findings: The results of this study provide insight into how entrepreneurship education influences career goals, attitudes towards self-employment as opposed to official employment, and how Business Studies help learners develop their entrepreneurial abilities. Additionally, it investigates the impact of contextual elements on incorporating entrepreneurial education into FET Business Studies learners’ career decision-making processes, including socioeconomic background, cultural norms, and institutional support.Practical Implications: Early introduction of Business Studies in the General Education and Training (GET) phase (Grades 8 and 9) will facilitate the easy transition of learners from the economic and Management Science (EMS) subject to Business Studies and encourage their interest in entrepreneurship.Social Implications: To foster learners’ interest in entrepreneurship, policymakers would need to support economic development in South Africa, where unemployment is extremely high, and recognise entrepreneurship as a crucial component for aspiring entrepreneurs.Originality and Value: This study added to our understanding of how Business Studies learners’ intentions to pursue entrepreneurship may be influenced by their entrepreneurship education. Additionally, this study raised awareness that, despite the numerous impediments to South Africa's development, entrepreneurship is still the best way to sustain growth in the twenty-first century and that learners should be encouraged to pursue it as a substitute for traditional job creation methods.
Keywords: Business studies. career choice. decision making. entrepreneurship education. South Africa